Indonesian Sastra Liar: Political Strategies of Social Movements in Indonesia - Sulton, Agus (Universitas Negeri Semarang, 2021)
This paper presents asastra liarstrategy in the beginning of 20th century in Indonesia. Those literature texts were created by the Marxism organizations. It aimed to be anti-government, anti-colonialism, anti-imperialism, and anti-capitalism propaganda. The historical methods used in this paper are divided into some phases: heuristic, source critics, interpretation, and historiography. As the result, this paper finds some propaganda strategies and politics used by the Left movement organizations in Dutch East Indies (Indonesia) to oppose the Dutch government and give education to the kromoor poor people. They did it in order to make Dutch East Indies an independence country, free from The Kingdom of Netherlands’ intervention, as soon as possible.